Effect of Manual System in Handling Documents Clearance in and Out Ship Service, Loading and Unloading Ship agency by PT. Bahari Eka Nusantara Sangkulirang branch, East Kalimantan - Roma Dormawaty; Ganda Toras Siregar; Nur Patria (Greenation Research & Yayasan Global Resarch National, 2023)
Bulk ship handling activities cannot be separated from the ship handling service plan, namely the arrival and departure of ships. Before the process of arrival and departure of the ship, several activities are carried out which are determined in advance by the shipping company together with the port manager and must be conveyed to the ship's side. The loading and unloading of ships coming and going, loading and unloading coal, requesting ship needs, handling clearance in and clearance out documents through Syahbandar manually whose service hours are limited, starting from 8 o'clock to 10 pm due to the shahbandar class which is still classified as KUPP class III, and also greatly limiting the movement and service of the ship service served. The purpose of this study is to find out how much influence the management of clearance documents in and out becomes longer, limited operating hours and delays in the loading and unloading process of ships, which are agentized by PT. Bahari Eka Nusantara Sangkulirang Branch, East Kalimantan. The approach method used is a descriptive quantitative method, while the data collection technique uses questionnaires, documentation, observations, and literature studies so that the influence / not between the manual clearance in and out system can be found on the service of the ship being inundated. The results of this study show that there is an influence between the manual clearance in and out system on the service of the ship being inundated.